Impact of early empirical antifungal therapy on prognosis of sepsis patients with positive yeast culture: A retrospective study from the MIMIC-IV database - Zou, Zhi-ye; Sun, Kai-jun; Fu, Guang; Huang, Jia-jia; Yang, Zhen-jia; Zhou, Zhi-peng; Ma, Shao-lin; Zhu, Feng; Wu, Ming (Frontiers in Microbiology, 2022)
Background Mortality and other clinical outcomes of culture-negative and culture-positive among patients with fungal sepsis have not been documented, and whether antifungal therapy prior to fungal culture reports is related to decreased mortality among patients remains largely controversial. This study aimed to determine the mortality and other clinical outcomes of patients with positive yeast cultures and further investigate the effects of initial empiric antifungal therapy. Methods A retrospective study was conducted among septic patients using the Medical Information Mart for Intensive Care (MIMIC)-IV database. Patients with sepsis were divided into two groups based on first fungal culture status during intensive care unit (ICU) stay, and initial empirical antifungal therapy was prescribed based on physician’s experience prior to fungal culture reports within 48 h. The primary outcome was in-hospital all-cause mortality. The secondary outcomes were 30-day all-cause mortality, 60-day all-cause mortality, length of ICU stay and length of hospital stay. Multivariate logistic regression, propensity score matching (PSM), subgroup analyses and survival curve analyses were performed. Results This study included 18,496 sepsis patients, of whom 3,477 (18.8%) had positive yeast cultures. Patients with positive yeast cultures had higher in-hospital all-cause mortality, 60-day all-cause mortality, and longer lengths of ICU stay and hospital stay than those with negative yeast cultures after PSM (all p < 0.01). Multivariate logistic regression analysis revealed that positive yeast culture was a risk factor for in-hospital mortality in the extended model. Subgroup analyses showed that the results were robust among the respiratory infection, urinary tract infection, gram-positive bacterial infection and bacteria-free culture subgroups. Interestingly, empiric antifungal therapy was not associated with lower in-hospital mortality among patients with positive yeast cultures, mainly manifested in stratification analysis, which showed that antifungal treatment did not improve outcomes in the bloodstream infection (odds ratio, OR 2.12, 95% CI: 1.16–3.91, p = 0.015) or urinary tract infection groups (OR 3.24, 95% CI: 1.48–7.11, p = 0.003). Conclusion Culture positivity for yeast among sepsis patients was associated with worse clinical outcomes, and empiric antifungal therapy did not lower in-hospital all-cause mortality in the bloodstream infection or urinary tract infection groups in the ICU.